2007
DOI: 10.2214/ajr.07.2489
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic Anatomy of the Inguinofemoral Region: Insights from MDCT

Abstract: MDCT produces images of the inguinal region in detail not possible with previous generations of scanners. In our small series, 100% identification of key anatomic structures was achieved when information from all three views was combined. We found subtle differences between imaging findings and standard anatomic teaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…It joins the anterosuperior iliac spine to the pubic tubercle (44)(45). Just lateral to this tubercle a V-shaped gap in the external oblique aponeurosis forms the external inguinal ring.…”
Section: A) Landmarksmentioning
confidence: 99%
See 2 more Smart Citations
“…It joins the anterosuperior iliac spine to the pubic tubercle (44)(45). Just lateral to this tubercle a V-shaped gap in the external oblique aponeurosis forms the external inguinal ring.…”
Section: A) Landmarksmentioning
confidence: 99%
“…MDCT produces images of the inguinal region with detail not available with previous generations of CT (44). When multiplanar reconstructions are performed in the sagittal , coronal and axial plane 100% identification of the key anatomic structures can be achieved (Fig.…”
Section: A) Landmarksmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that the inferior epigastric artery has been visible in 90% of the cases, especially on unenhanced computed tomography examinations (1). However, efficacy of such technology to visualize important anatomic structures found in the inguinal region was reported by several authors previously (12). In this study, it was possible to visualize the inferior epigastric artery and the vein, the inguinal ligament, the spermatic cord, the radiologic femoral triangle and the pubic tubercle in all cases.…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, accurate imaging is vital to ensure diagnosis of inguinal hernia in patients with such presentations (10,11). Scanner technology with multi-planar reformatting makes it possible to produce high resolution sagittal, coronal and oblique images in any plane from raw axial images that allows visualization of relevant anatomic structures (4,8,12,13). It is reported that the inferior epigastric artery has been visible in 90% of the cases, especially on unenhanced computed tomography examinations (1).…”
Section: Discussionmentioning
confidence: 99%